Determinants of Profitability in Indonesian Textile and Garment Firms: The Moderating Role of Exchange Rate - Tetuko, Flugor; Nurwati, Etty; Purwanto, Sri; Pangestuti, Dewi Cahyani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effects of capital structure, working capital, liquidity, and firm size on profitability, with the exchange rate serving as a moderating variable in textile and garment companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research is motivated by increasing financial pressure and exchange rate uncertainty faced by manufacturing industries in emerging economies. Panel data regression using the Fixed Effect Model combined with Moderated Regression Analysis is employed to analyze firms’ financial data. The findings indicate that capital structure, working capital, and firm size have a positive and significant impact on profitability, while liquidity does not exhibit a significant direct effect. Furthermore, the exchange rate moderates the relationship between capital structure and liquidity on profitability and weakens the influence of firm size on profitability. However, the exchange rate does not moderate the relationship between working capital and profitability. These results highlight the importance of adaptive financial management and heightened awareness of exchange rate risk in sustaining profitability within the textile and garment industry. Keywords: capital structure, working capital, liquidity, firm size, profitability, exchange rate)